Effect of crocodile oil (Crocodylus siamensis) on brain mitochondrial protein expression and cognition in male rats - Krittika Srisuksai; Kongphop Parunyakul; Pitchaya Santativongchai; Sumate Ampawong; Phitsanu Tulayakul; Wirasak Fungfuang (Penerbit Universiti Kebangsaan Malaysia, 2023)
Crocodile oil (CO) is rich in polyunsaturated (PUFAs) fatty acids. Diets rich in PUFAs can maintain mitochondrial function, which is important in signal transduction and survival of neuronal cells. We investigated the effects of CO on brain mitochondrial protein expression and cognitive function in male rats. Twenty-one rats were randomly divided into three groups: (1) control, (2) treated with CO (3 mL/kg), and (3) treated with palm oil (PO; 3 mL/kg). Animals received oral gavage once-daily for seven weeks. The parameters that were measured were food intake, energy intake, body weight, serum lipid profiles, cognitive behavior, brain mitochondrial architecture, brain mitochondrial expression, and hippocampal structure. In CO and PO groups, food intake decreased significantly compared with that in the control group (p<0.05), but energy intake, body weight, and lipid profiles were not affected. Spatial learning in the PO group decreased significantly compared with that in control and CO groups (p<0.05). Crocodile oil significantly decreased the percentage of abnormal mitochondria (p<0.05) and the expression of apoptotic marker (p<0.05) compared with those in the PO treatment but also increased energy production marker (p<0.05) compared with those in the control and PO treatment. Moreover, percentage of intact hippocampal cells was not different between CO and control groups, but neuronal cells were lost in the PO group (p<0.05). This study suggest that CO could enhance the brain energy production and maintain cognitive function. CO can be an alternative dietary oil for treating brain energy disorder in the future.